2003
DOI: 10.1021/la026923k
|View full text |Cite
|
Sign up to set email alerts
|

Generation Mechanism of Shear Yield Stress for Regular Defect Arrays in Water-in-Cholesteric Liquid Crystal Emulsions

Abstract: We have investigated the rheological behavior of the quadrilateral defect array formed in cholesteric emulsions, which are composed of water, surfactants, and cholesteric liquid crystals. The defect array is spontaneously formed after stopping the shear to the cholesteric emulsions, between glass plates with a homeotropic anchoring surface. In the formation process of the defect array, Newtonian flow behavior was detected immediately after termination of the preshear; however, the shear yield stress appeared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Our results can be illuminated by considering the bulk shear rheology of cholesterics undergoing permeation flow along the pitch direction. In this case, in any finite sample there is a regime of linear rheology, but the shear viscosity increases linearly with system size, diverging in the thermodynamic limit [18,19]. Crudely treating the colloid radius R as an effective sample size then gives α = 2, not far from the observed value (α ≈ 1.7).…”
mentioning
confidence: 92%
“…Our results can be illuminated by considering the bulk shear rheology of cholesterics undergoing permeation flow along the pitch direction. In this case, in any finite sample there is a regime of linear rheology, but the shear viscosity increases linearly with system size, diverging in the thermodynamic limit [18,19]. Crudely treating the colloid radius R as an effective sample size then gives α = 2, not far from the observed value (α ≈ 1.7).…”
mentioning
confidence: 92%
“…Thus induced distortion of the liquid crystalline order assumes a dipolar property, which leads to the chain formation owing to the balance of long-range dipolar attractive and short-range defectmediated repulsive interactions. In other systems of LC emulsions, there are some attractive reports about spontaneously formed three-dimensional defect structures, which are composed of water droplets and nematic [2] or cholesteric fluids [4,10]. Liquid-crystal dispersions can be thus expected to show further new liquid-crystal structures and unique phenomena [11], owing to the interparticle and/or particle-LC interactions.…”
mentioning
confidence: 99%
“…In most of these theoretical studies it was found that monodomain nematic liquid crystals are viscoelastic in a frequency region surrounding the director relaxation time, and that the response in the small frequency terminal region corresponds to pure viscous material. Obviously, introduction of stable defect lattices would predict elastic response in the terminal zone, as observed by Ramos et al [15] and by Yada et al [16] for cholesteric liquid crystals. In this paper we show that the relatively simple SAOF measurements are also a useful tool to determine flow alignment in liquid crystals.…”
Section: Introductionmentioning
confidence: 72%